Unsatisfactory Ecranisation Of Lasse Hallstrom's Dear John Novel (2006) A Reader Response Analysis - Yanudiasti, Wulan; , Dr. M. Thoyibi. M.S (2016)
This research aims to analyze the dissatisfaction of the readers and reviewers about Dear John movie. This movie is adapted from Dear John novel written by Nicholas Sparks. The movie has a different ending with the novel. It makes the readers and reviewers feel disappointed with the movie. This research employs reader response approach. The type of this research is descriptive qualitative. The researcher gets the data from the novel, includes the narration, monologue, and dialogue. The techniques of collecting the data are note taking which takes only the point of the source. The technique of data analysis is descriptive interactive which comprises three procedures, namely: data reduction, data display, and conclusion. The results show the following conclusions: the dominant issues of the movie include the acting of player, plot or story, message, theme, and soundtrack of the movie; the background of the readers and reviewers includes country, year of response, and gender of the readers and reviewers, and there are differences between the novel and the movie